Aqueous extract from You-Gui-Yin ameliorates cognitive impairment of chronic renal failure mice through targeting hippocampal CaMKIIα/CREB/BDNF and EPO/EPOR pathways. (15th July 2019) - Tang, Qing; Ke, Hui; Wu, Chao; Zeng, Jie; Li, Zhuohen; Liu, Yang; Feng, Shan; Xue, Qiang; Xu, Xiaoyu
Abstract: Ethnopharmacological relevance: You-Gui-Yin (YGY) is a traditional Chinese recipe used for reinforcing kidney essence which is recorded in Jingyue Quanshu written by Zhang Jingyue in Ming dynasty. According to traditional Chinese medicine theory, kidney essence is associated with brain and without sufficient kidney essence, cognitive impairment may occur. Aim of the study: In this study, we aimed to investigate the effect of YGY extract on cognitive impairment of chronic renal failure (CRF) mice and explore the mechanisms involved. Materials and methods: Aqueous extract of YGY was prepared from crude drugs and was quality controlled by high-performance liquid chromatography (HPLC). CRF was induced by 0.2% adenine in mice and CRF mice were intragastrically administered with 1.5 g kg −1, 3.0 g kg −1, and 6.0 g kg −1 of YGY extract. Mice were identified with CRF by determining several biochemical and physiological indexes, including creatinine clearance rate, serum creatinine, serum urea nitrogen, serum Ca, serum P, serum Mg, body weight and body temperature. Morris water maze and novel object recognition tests were conducted for evaluation of cognitive function. In addition, changes of CaMKIIα/CREB/BDNF and EPO/EPOR pathways in hippocampus were examined by detecting the protein expressions of CaMKIIα, p-CaMKIIα (Thr286), CREB1, p-CREB1 (Ser133), BDNF, EPO, EPOR, p-EPOR (Tyr485), STAT5, and AKT1 using western blotting assays. Also, the primary EPO-producing cells in brain (i.e. astrocytes) and EPO expression regulator HIF-2α were checked by fluorescence microscopy and western blotting assay, respectively. Results: Nine components in YGY extract were figured out and monitored with their contents by HPLC for the quality control of YGY extract. Biochemical and physiological measurements validated the success of induction of CRF in mice, and YGY extract significantly retarded the CRF progression and ameliorated the CRF-induced cognitive impairment. The behavioral tests showed that compared with normal control mice, CRF mice had impaired cognitive function. However, treatment of YGY extract significantly ameliorated the cognitive impairment of CRF mice. Additionally, decreased expressions of hippocampal CaMKIIα, p-CaMKIIα (Thr286), CREB1, p-CREB1 (Ser133), and BDNF were observed in the hippocampus of CRF mice, but YGY extract significantly restored these protein expressions. Moreover, hippocampal EPO, EPOR, p-EPOR (Tyr485), STAT5, AKT1, and HIF-2α, as well as the number of astrocytes in CA1 zone of hippocampus were also decreased in CRF mice, while YGY extract prominently promoted the expressions of these proteins and increased the number of astrocytes. Conclusions: All the data in this study suggested that YGY extract ameliorated the cognitive impairment of CRF mice, and this amelioration was related to up-regulating the CaMKIIα/CREB/BDNF and EPO/EPOR pathways. Graphical abstract: Image 1